Managing Data Quality A practical guide. - King, Tim (BCS Learning & Development Limited, 2020)
This book explains data quality management in practical terms, focusing on three key areas - the nature of data in enterprises, the purpose and scope of data quality management, and implementing a data quality management system, in line with ISO 8000-61.